Proses Peralihan Hak Guna Bangunan Berdasarkan Jual Beli Dibawah Tangan yang tidak Diketahui Keberadaan Pemiliknya (Studi Putusan Pengadilan Negeri Pontianak No. 92/Pdt.G/2021/PN.PTK) - Simatupang, Patumona Febriyanty; Anggoro, Teddy (Wajah Hukum, 2025)
Underhand sales transactions used for the transfer of Building Use Rights (HGB) often result in various legal issues, especially when the whereabouts of the original certificate owner are unknown. This research focuses on analyzing the District Court Decision No. 92/Pdt.G/2021/PN PTK, which examines the legality of HGB transfers within the framework of agrarian law in Indonesia. In this case, the registration of the transfer of rights must comply with existing regulations, including obtaining approval from the legitimate owner. The court's decision takes into account several factors such as agreements between parties, good faith, and the registration of land rights. This research aims to examine the legality of the transfer of Building Use Rights (HGB) through an underhand sale based on the District Court Decision No. 92/Pdt.G/2021/PN PTK, in accordance with Indonesian agrarian law. The analysis reveals that although underhand sales can be considered valid under certain conditions, the absence of formal procedures can result in legal disadvantages for uninvolved parties. This research also highlights the importance of land registration to ensure legal protection for all involved parties. Additionally, the study underscores the need to understand the legal aspects of the transfer of building use rights and the risks associated with transactions that do not comply with the procedures prescribed by law.